Microcredit versus Child Schooling Nexus: Exploring Child Schooling Decisions in Rural Bangladesh (The Pakistan Development Review, 2024)
The study investigates if the microfinance loan burden influences the children’s education of the borrowers. By surveying the microfinance borrowers of Agarpur and Thakurmollik— distant rural areas under the Barisal district (Southern part of Bangladesh)— and by applying the OLS regression technique and logistic regression technique, the study identifies that the amount of microfinance loan installment does not have any significant direct effect on the dropout or enhancement of child education. Instead, the dropout tendency increases as kids move from primary to secondary or higher secondary level or as the number of kids increases in the family. However, as more kids are going to primary school, the school dropout tendency decreases. Thus, in remote rural areas, children’s school dropout appears as a matter of social behaviour rather than being an issue of microfinance loan burden.